Chronic Kidney Disease Increases Risk for Venous Thromboembolism - Wattanakit, Keattiyoat (American Society of Nephrology, 2008)
Chronic kidney disease (CKD) is associated with increased risk for cardiovascular disease morbidity and mortality, but its association with incident venous thromboembolism (VTE) in non–dialysis-dependent patients has not been evaluated in a community-based population. With the use of data from the Longitudinal Investigation of Thromboembolism Etiology (LITE) study, 19,073 middle-aged and elderly adults were categorized on the basis of estimated GFR, and cystatin C (available in 4734 participants) was divided into quintiles. During a mean follow-up time of 11.8 yr, 413 participants developed VTE. Compared with participants with normal kidney function, relative risk for VTE was 1.28 (95% confidence interval [CI] 1.02 to 1.59) for those with mildly decreased kidney function and 2.09 (95% CI 1.47 to 2.96) for those with stage 3/4 CKD, when adjusted for age, gender, race, and center. After additional adjustment for cardiovascular disease risk factors, an increased risk for VTE was still observed in participants with stage 3/4 CKD, with a multivariable adjusted relative risk of 1.71 (95% CI 1.18 to 2.49). There was no significant association between cystatin C and VTE. In conclusion, middle-aged and elderly patients with CKD (stages 3 through 4) are at increased risk for incident VTE, suggesting that VTE prophylaxis may be particularly important in this population.